Misi Gereja dalam Budaya Digital: Integrasi Kepemimpinan Holistik dan Inkulturasi Injil - Elisa Nimbo Sumual; Yohana Fajar Rahayu (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
The development of digital culture has fundamentally changed the way humans communicate and build relationships. It has even changed the way humans express their faith. The church no longer only deals with physical space, but also with virtual or digital space, which shapes the way congregations understand spiritual authority, spirituality, and the practice of faith. However, the Church's mission in digital culture is often carried out instrumentally without adequate theological integration between church leadership and the inculturation of the Gospel. The phenomenon of increasing religious activity in digital media, accompanied by the fragmentation of spirituality and the commodification of the Gospel message, points to the urgency of a deeper theological reflection on the digital mission of the Church. This study aims to analyse how the integration of holistic leadership and the inculturation of the Gospel can shape contextual and transformative church mission practices in digital culture. This study uses qualitative methods with a conceptual theological approach and critical literature analysis of studies on mission theology, pastoral care, and digital culture. The results of the study show that digital culture needs to be understood as a mission context that demands an inculturative approach, not merely a technological means. Holistic leadership acts as a theological agent that bridges the Gospel and digital culture in a critical and reflective manner. The integration of the two enables the church to present a mission that is relevant, faithful to the Gospel, and transformative in the digital age.AbstrakPerkembangan budaya digital telah mengubah secara mendasar cara manusia berkomunikasi dan juga membangun relasi. Bahkan mengubah manusia dalam mengekspresikan iman.  Gereja tidak lagi hanya berhadapan dengan ruang fisik, tetapi juga dengan ruang virtual atau digital yang membentuk cara umat memahami otoritas rohani, spiritualitas, dan praksis keimanan. Namun, praktik misi gereja dalam budaya digital kerap dijalankan secara instrumental tanpa integrasi teologis yang memadai antara kepemimpinan gereja dan inkulturasi Injil. Fenomena meningkatnya aktivitas keagamaan di media digital, disertai fragmentasi spiritualitas dan komodifikasi pesan Injil, menunjukkan urgensi refleksi teologis yang lebih mendalam terhadap misi gereja digital. Penelitian ini bertujuan untuk menganalisis bagaimana integrasi kepemimpinan holistik dan inkulturasi Injil dapat membentuk praksis misi gereja yang kontekstual dan transformatif dalam budaya digital. Penelitian ini menggunakan metode kualitatif dengan pendekatan teologi konseptual dan analisis literatur kritis terhadap kajian teologi misi, pastoral, dan budaya digital. Hasil kajian menunjukkan bahwa budaya digital perlu dipahami sebagai konteks misi yang menuntut pendekatan inkulturatif, bukan sekadar sarana teknologis. Kepemimpinan holistik berperan sebagai agen teologis yang menjembatani Injil dan budaya digital secara kritis dan reflektif. Integrasi keduanya memungkinkan gereja menghadirkan misi yang relevan, setia pada Injil, dan berdaya transformatif di era digital.